2022
DOI: 10.3390/nu14112215
|View full text |Cite
|
Sign up to set email alerts
|

Increased Breastfeeding Proportion Is Associated with Improved Gross Motor Skills at 3–5 Years of Age: A Pilot Study

Abstract: Breastmilk provides key nutrients and bio-active factors that contribute to infant neurodevelopment. Optimizing maternal nutrition could provide further benefit to psychomotor outcomes. Our observational cohort pilot study aims to determine if breastfeeding extent and breastmilk nutrients correlate with psychomotor outcomes at school age. The breastfeeding proportion at 3 months of age and neurodevelopmental outcomes at 3–5 years of age were recorded for 33 typically developing newborns born after uncomplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…The active muscle tone in the high-proportion breast milk feeding group was higher than that in the low and medium-proportion groups. Research has shown that the more breastfeeding, the stronger the ability to perform large muscle movements and solve problems, which is consistent with our findings [ 27 ]. However, our results show no differences in selective posture control, midline alignment, motor quality, or behavioral ability among high-proportion breast milk feeding groups, which needs further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…The active muscle tone in the high-proportion breast milk feeding group was higher than that in the low and medium-proportion groups. Research has shown that the more breastfeeding, the stronger the ability to perform large muscle movements and solve problems, which is consistent with our findings [ 27 ]. However, our results show no differences in selective posture control, midline alignment, motor quality, or behavioral ability among high-proportion breast milk feeding groups, which needs further investigation.…”
Section: Discussionsupporting
confidence: 93%